Pertumbuhan berbagai Macam Bahan Eksplan Kentang Atlantik secara In Vitro dengan Perlakuan IAA - Anisah Shofhatur Rohmah; Ellen Rosyelina Sasmita; Endah Wahyurini (Universitas Sebelas Maret, 2021)
The Atlantic potato is the potato used in the food industry. Conventional potato propagation is constrained by the accumulation of pathogens, decreased quality of seed, and low propagation rates. Plant tissue culture is one of the appropriate method that can be used to solve these problem. This study aims to determine the most appropriate IAA concentration for various kinds of Atlantic potato explants. The study was conducted in July - August 2020 at the Tissue Culture Laboratory of the Pembangunan Nasional Veteran Yogyakarta University. Completely Randomized Design (CRD) was used as an experimental design with different combination of the concentration of IAA at 0,5; 1; and 1,5 ppm and the kind of explants namely shoot, middle, and base of the plantlet). Observation was conducted at 8 weeks after planting. Variables observed were plantlet height, number of nodes, number of branches, number of leaves, leave colour, root length, and dry weight of plantlet. The results showed that 1 ppm concentration of IAA with the middle of the plantlet could increase the number of node and the number of leaves of Atlantic potato plantlets. 0.5 ppm concentration of IAA were able to increase the plantlet height, number of branches, root length, and dry weight of Atlantic potatoes. Explants from the middle of the plantlet were able to increase the number of side shoots of Atlantic potato plantlets.